Isolated penile urethral injury: A rare case following male coital trauma - Ka Wing Wong; Brian Sze Ho Ho; Chi Ho Ip; Ming Kwong Yiu (Asian Journal of Urology)
Penile fractures are an uncommon urological emergency. Typically, penile fractures involve the corpus cavernosum and are sometimes associated with urethral injury. Isolated corpus spongiosum and urethral injuries without concomitant corpus cavernosum injury are, however, rare. With proper knowledge of the management of penile fractures and urethral injuries, this distinct entity can be diagnosed, assessed and managed successfully without complications.